PROPOSAL TO ADJUST THE DATA STRUCTURE OF NATIONAL DATABASE OF RESOURCES, ENVIRONMENT OF SEAS AND ISLANDS - Hung, Vo Xuan; Hanh, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2015)
Recognising the limitations encountered during the operation of the national database of resources, environment of seas and islands, the article proposed to adjust the data structure of this database aiming at easily updating, managing and distributing the existing data as well as new data, improving the quality and reliability of the data but not disturbing the status quo. This adjustment has not only been established in accordance with other maritime countries and international institutions of marine data, but also taken into account the characteristics of the data and the current management model of Vietnam. This proposal aimed at completing national database of resources, environment of seas and islands, making it more dynamic, easily updated and manageable with important, diversified and abundant data sources, in natural resources, marine and island environment of Vietnam, being worthy of a national database. The proposal is the result of the Cooperation Protocol with the United States “Researches on building database, standards, and documentation in the sea of Vietnam” of Vietnam Ocean Data and Information Center (VODIC).